2014
DOI: 10.4103/0970-4388.130996
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic improvement of white spot lesions and non-pitted fluorosis using resin infiltration technique: Series of four clinical cases

Abstract: White opacities have always been a major concern of esthetics for patients and can have varying etiology. In general, white discolorations of enamel might be due to dental fluorosis, early caries (white spot lesions), developmental defects etc. Conventional treatment options available for such opacities include non-invasive and invasive approaches. Recently, a new "micro-invasive" technique has been introduced as an alternative therapeutic approach that improves such opacities esthetically, in a single sitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 0 publications
2
25
0
3
Order By: Relevance
“…Likewise, one of research papers has detailed on ‘immediate esthetic changes in fluorosis’ and have shown that many a times patients do get ‘satisfied’ with immediate esthetic changes itself without requesting for any further treatment . Moreover, one of the main intervention strategy used in this study was RI, which has already demonstrated its efficacy for bringing immediate esthetic changes for carious opacities with stable results on long term basis too and using RI for fluorosis is adding a new indication for this novel technique . Hence, it was considered important to study the immediate esthetic changes initially.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, one of research papers has detailed on ‘immediate esthetic changes in fluorosis’ and have shown that many a times patients do get ‘satisfied’ with immediate esthetic changes itself without requesting for any further treatment . Moreover, one of the main intervention strategy used in this study was RI, which has already demonstrated its efficacy for bringing immediate esthetic changes for carious opacities with stable results on long term basis too and using RI for fluorosis is adding a new indication for this novel technique . Hence, it was considered important to study the immediate esthetic changes initially.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, one of the main intervention strategy used in this study was RI, which has already demonstrated its efficacy for bringing immediate esthetic changes for carious opacities with stable results on long term basis too and using RI for fluorosis is adding a new indication for this novel technique. 17,30 Hence, it was considered important to study the immediate esthetic changes initially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the aspect of WSL and early caries treatment, several other investigators also described an esthetical improvement and mechanical stabilization of fluorotic teeth, traumatic white spots or teeth suffering from molar incisior hypomineralisation (MIH) by infiltration, which increases its use as a therapeutic alternative for esthetic purposes in different types of porous lesions (51)(52)(53)(54)(55)(56) . E.g., Kim et al (41) described the effects of infiltration on teeth with developmental enamel defect and post-orthodontic WSL.…”
Section: Post-orthodontic Wsl In Vivomentioning
confidence: 99%